Advances in the role of lysophosphatidyl-choline acyltransferase 1 in tumors - CHEN Xue, LUO Tian, WEI Chaojun (Jichu yixue yu linchuang, 2024)
Lysophosphatidylcholine acyltransferase 1(LPCAT1), a key metabolic enzyme in the phosphatidyl-choline metabolism pathway, mediates phosphatidylcholine synthesis through deacylation-reacylation, which leads to alterations in the phospholipids composition of cell membranes and the remodelling of the cellular cytoskeleton. Lysophosphatidylcholine acyltransferase 1 has been shown to be highly expressed in gastric, breast and colorectal cancer, and can accelerate the alteration of the phospholipids composition of tumor cell membranes or interact with tumor driver genes, such as epidermal growth factor receptor and cell cycle-related genes. It might promote tumor development by affecting tumor cell proliferation, migration, invasion and resistance to chemotherapy.